Cloning and Expression of Recombinant Nucleoprotein of Influenza H1N1 - Tavakoli, Somaie; Bandehpour, Mojgan; Soleimanifar, Zeinab; Goudarzi, Mehdi; Kazemi, Bahram (Novelty in Biomedicine, 2015)
Background: Influenza virus is the major cause of lower respiratory tract illnesses on the worldwide. Vaccination can be an effective tool to prevent its outbreak. Highly conserved viral nucleoprotein is an effective vaccine candidate to provide heterosubtypic immunity, offering resistance against various influenza virus strains. Materials and Methods: In present research NP gene was inserted in pET-22b expression vector. New construct (pET-22b/NP) was transformed into E. coli BL21 (DE3) strain and the expression of nucleoprotein was induced by IPTG. It was analyzed by SDS-PAGE and confirmed by Western blotting. Results: Western blotting confirmed the expression and production of recombinant Influenza nucleoprotein. Conclusion: These results suggest that the codon-optimized influenza A virus NP gene can be efficiently expressed in E. coli.